2018
DOI: 10.15171/jhp.2018.40
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effect of Descurainia sophia seed extract against paracetamol-induced oxidative stress and hepatic damage in mice

Abstract: Results demonstrate that D. sophia seed extract is able to limit the paracetamol-induced oxidative and hepatic damages in the liver. Further studies are required to confirm the mechanisms responsible for hepatoprotective activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The mechanism of acetaminophen-induced nephrotoxicity and hepatotoxicity has been reported by other investigators and showed that paracetamol causes oxidative stress and renal toxicity when used at high doses (21)(22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 63%
“…The mechanism of acetaminophen-induced nephrotoxicity and hepatotoxicity has been reported by other investigators and showed that paracetamol causes oxidative stress and renal toxicity when used at high doses (21)(22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 63%
“…Additionally, many other cellular processes such as endoplasmic reticulum stress, autophagy, sterile inflammation, microcirculatory dysfunction, and liver regeneration have been identified to be involved in the pathogenesis of APAP-induced liver injury [ 44 ]. Necrosis, vacuolar degeneration, and inflammatory cell infiltration were also seen after APAP administration [ 52 ]. Degrees of both necrosis and vacuolar degeneration were higher in the negative control group, which received only APAP compared with a normal control group in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the moderate ash content may clearly implicate in the treatment and management of drug-induced toxicity. Acetaminophen (APAP), a commonly used analgesic, and the antipyretic drug are metabolized by CYP450 enzymes to give N-acetyl-P benzoquinone-imine at extreme doses correspondingly causing covalent binding to thiol groups of reduced glutathione in the liver and kidney, depleting glutathione, and increasing the risk for hepatotoxicity [ 33 ].…”
Section: Discussionmentioning
confidence: 99%